Ada Apa Dengan Profesi Akuntan di Era Transformasi Digital? - Muh. Achsan Maulana; Baso Ahmad Fajar; Nurfadillah Annisa Arifin (Academic Bright Collaboration, 2023)
What's Happening to the Accounting Profession in the Era of Digital Transformation? This research aims to find out how the accounting profession is experiencing technological transformation in the digital era. The method used by the analytical tool is a metasynthesis of a number of qualitative studies on the current condition of the accounting profession. The results of this research provide a new view regarding the obstacles, advantages, challenges and opportunities faced by the accounting profession in the digital era. Accountants face barriers regarding the use of technology, which involves adapting their skills and experience. The challenges in implementing this technology include technical aspects, skills, ethics and data security of accountants. The application of automation technology brings a number of conveniences in increasing efficiency, accuracy and other conveniences for accountants. The opportunity presented in this transformation is to make the work of accountants easier and more efficient, but it also poses a threat of accountants being replaced by technology.